The Effect of Infrastructure Management and Tutor Recruitment on The Quality of Community Learning Activities Center (CLAC) Graduates - Ipong Dekawati; Ike Medyawati Setiarini; Rizki Satria Nugraha (Universitas Ahmad Dahlan, 2022)
This study aims to determine how much influence infrastructure management and tutor recruitment partially or jointly have on the quality of graduates in CLAC. The research was conducted using a descriptive correlational method with a quantitative approach. The analysis was carried out by distributing questionnaires to 50 respondents who were the samples in this study. The results of this study reveal that it can be concluded that: 1) There is a significant influence of infrastructure management on the quality of graduates in CLAC. 2) There is a significant effect of tutor recruitment on the quality of graduates in CLAC. 3) There is a significant influence of infrastructure management and tutor recruitment on the quality of graduates in CLAC. The magnitude of infrastructure management and tutor recruitment influences the quality of graduates in CLAC; this study strengthens and proves or is in line with several experts and researchers. Previous writers stated that the quality of graduates was heavily influenced by infrastructure management.